Pengaruh Beban Kerja, Disiplin Kerja, Dan Lingkungan Kerja, Terhadap Kinerja Karyawan Pada Mr Egg X Messa Club Bali Di Canggu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
This research was conducted to analyze the influence of workload, work discipline, and work environment on employee performance at Mr Egg X Messa Club Bali in Canggu. The method used in this activity was a quantitative approach with the support of all 96 employees registered by means of saturated sampling techniques. Data in this study were sought and collected through observation, questionnaires, and literature studies, including documentation activities. The data obtained were then analyzed using multiple linear regression. The results of this study provide evidence that workload, work discipline, and work environment have a positive influence that also causes significant changes both partially and simultaneously on employee performance. Work discipline has also been proven to provide evidence with the results of its most dominant influence. The implications of this research have succeeded in realizing the importance of proportional workload management, increasing discipline through supervision and rewards, and also creating a conducive work environment to help improve employee performance continuously.